Impact of grading capacitor on transient recovery voltage due to shunt reactor de-energization for different values of current chopping - Al-Tak, Mazyed A.; Ain, Mohd Fadzil; Al-Yozbaky, Omar Sh.; Jamil, Mohamad Kamarol Mohd (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper investigates the impact of grading capacitors on transient recovery voltage (TRV) during shunt reactor switching in high voltage systems, considering different levels of current chopping. Shunt reactor de-energization can result in voltage surges and instability due to current chopping effects. The study utilizes simulation models using ATP-Draw software to assess the effectiveness of grading capacitors in mitigating TRV under various operating conditions as well as of using a proposed method to mitigate the excessive TRV across the circuit breaker. The findings provide valuable insights into managing TRV during shunt reactor switching, enhancing power system stability and reliability. The results obtained showed that the TRV across the circuit breaker decreased by 61.5% by using circuit modification as well as adding a grading capacitor.